2008
DOI: 10.1111/j.1600-0404.2007.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of hippocampal neurogenesis in streptozotocin-treated diabetic rats

Abstract: Objectives –  Adult neurogenesis in dentate gyrus (DG) is an evolutionarily preserved trait in most mammals examined thus far. Neuronal proliferation and subsequent integration of new neurons into the hippocampal circuit are regulated processes that can have profound effects on an animal’s behaviour. A streptozotocin model of type I diabetes, characterized by low insulin and high plasma glucose levels, affects not only body’s overall metabolism but also brain activity. Materials and methods –  Neurogenesis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 30 publications
2
94
2
3
Order By: Relevance
“…Increasing evidence points toward an association between diabetes mellitus and deficit in learning and memory. [5,7] Findings of the research and evidences in the literature revealed reduced neurogenesis in the dentate gyrus of diabetic hippocampus [8] and decreased dendritic arborization. [9] Stress exposure triggered fear memory and anxiety, and decreased the hippocampal-dependent memory performance in mice.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 85%
“…Increasing evidence points toward an association between diabetes mellitus and deficit in learning and memory. [5,7] Findings of the research and evidences in the literature revealed reduced neurogenesis in the dentate gyrus of diabetic hippocampus [8] and decreased dendritic arborization. [9] Stress exposure triggered fear memory and anxiety, and decreased the hippocampal-dependent memory performance in mice.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 85%
“…administration of STZ (0.1 ml volume) for five consecutive days at a dose of 50 mg STZ/kg body weight. Body weight and blood glucose levels (determined from tail blood by glucometer) were monitored once every two days during the STZ treatment week and thereafter once weekly for the rest of the study [13][14][15]. OA treatment was performed by subcutaneously implanted ALZET Micro-osmotic pumps (Model 1004, Alzet, Cupertino, CA) at a rate of 3.5 pM/kg/min.…”
Section: Establishment Of Tau Hyperphosphorylation Rat Modelmentioning
confidence: 99%
“…The drug STZ induction into the body causes decreased insulin discharge by destructing the b-cells of the pancreas in the islets of Langerhans. With the help of minute quantity of left over insulin in the pancreas animal can survive for several months but, the disease is fatal without any treatment (Zhang et al, 2008). Highly signifi cant nissl body damage was seen in the motor cortex neurons of rats in DI+S group when compared to the NC rats.…”
Section: Effect Of Ee On the Combined Actions Of Diabetes And Stress mentioning
confidence: 99%